2015
DOI: 10.1128/jvi.02008-15
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Regulates Lytic Activation of Kaposi's Sarcoma-Associated Herpesvirus

Abstract: Lytic activation of Kaposi's sarcoma-associated herpesvirus (KSHV) from latency is a critical contributor to pathogenesis and progression of KSHV-mediated disease. Development of targeted treatment strategies and improvement of lytic-phase-directed oncolytic therapies, therefore, hinge on gaining a better understanding of latency-to-lytic-phase transition. A key observation in that regard, also common to other herpesviruses, is the partial permissiveness of latently infected cells to lytic-cycle-inducing agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 45 publications
2
56
1
Order By: Relevance
“…Interestingly, inhibition of STAT3 activation promoted HIV-1 Tat-dependent KSHV lytic reactivation56, supporting our observations that STAT3 may function as an inhibitor of the lytic cycle. A recent study showed that inhibition of STAT3 in PEL cells enhances KSHV lytic replication and correlates with our findings57. We have also extended this to further demonstrate a potential strategy for elimination of latent cells using a combination of a STAT3 inhibitor and ganciclovir (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, inhibition of STAT3 activation promoted HIV-1 Tat-dependent KSHV lytic reactivation56, supporting our observations that STAT3 may function as an inhibitor of the lytic cycle. A recent study showed that inhibition of STAT3 in PEL cells enhances KSHV lytic replication and correlates with our findings57. We have also extended this to further demonstrate a potential strategy for elimination of latent cells using a combination of a STAT3 inhibitor and ganciclovir (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…The control of the latent and lytic phases of herpesviruses is a complex interplay and orchestration between viral and host factors. Host factors such as STAT3 (21), KAP1/TRIM28 (22), retinoblastoma (Rb) (23), and the cellular peptidyl-prolyl cis/trans isomerase Pin1 (24) were recently found to play very important roles in this latent-tolytic life cycle switch of herpesviruses.…”
mentioning
confidence: 99%
“…KAP1 restricts HIV1 integration (Allouch et al, 2011), and maintains latency for KSHV (Cai et al, 2013; Gjyshi et al, 2015; King et al, 2015; Sun et al, 2014; Zhang et al, 2014), EBV (Bentz et al, 2015), and HCMV (Rauwel et al, 2015). Phosphorylation of KAP1 decreases its ability to induce heterochromatin and triggers reactivation of HCMV (Rauwel et al, 2015).…”
Section: Epigenetics and Viral Chromatinmentioning
confidence: 99%
“…The LANA-KAP1 complex was found to associate with the viral immediate early control region upstream of the viral immediate early transcriptional activator (RTA) gene (Sun et al, 2014) and regulate the hypoxia response pathway mediated by the transcriptional regulators HIF1α and RBP-jK (Zhang et al, 2014). Modulation of the KAP1 pathway by the transcription factors NRF2 (Gjyshi et al, 2015), and STAT3 (King et al, 2015) also contribute to KSHV latent to lytic switch, further highlighting the central role of KAP1 in regulating viral latency.…”
Section: Epigenetics and Viral Chromatinmentioning
confidence: 99%